A multi-level pore defective carbon supported single-atom oxygen reduction electrocatalyst and a preparation method thereof

CN117613288BActive Publication Date: 2026-10-23SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311375883.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2026-10-23
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

[0004]鉴于上述现有技术的不足,本发明的目的在于提供一种多级孔缺陷碳负载单原子氧还原电催化剂及其制备方法,旨在解决现有氧还原电催化剂的原子利用率低以及催化活性较差的问题

Benefits of technology

[0013]有益效果:与现有技术相比,本发明提供了一种多级孔缺陷碳负载单原子氧还原电催化剂的制备方法,首先利用NH4Cl在高温下分解为NH3和HCl,ZIF-8作为一个酸敏感性材料,分解过程中形成的HCl可对其进行刻蚀,加上Zn的离开,最终可形成多孔结构的氮掺杂碳;然后在室温下,Fe3+可以与孔表面的空位结合,形成稳定的Fe-N结构,随后,将吸附有金属离子的碳材料再次在惰性气氛中还原,即可实现氮掺杂的多孔碳表面的Fe-N4的原子级分散,即制得多级孔缺陷碳负载单原子氧还原电催化剂。本发明中Fe以单原子形式均匀分散到碳基底上而没有Fe的金属颗粒存在,表明Fe完全掺杂进入碳结构中,多孔结构的存在有利于Fe-N4活性位的暴露,从而可提高催化剂的氧还原性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117613288B_ABST
    Figure CN117613288B_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-level hole defect carbon load single atom oxygen reduction electrocatalyst and preparation method thereof, wherein, preparation method includes the following steps: ZIF-8 containing NH4Cl is treated by high-temperature pyrolysis, and the porous structure of nitrogen-doped carbon is obtained;The porous structure of nitrogen-doped carbon is immersed into the solution containing ferric chloride, and the nitrogen-doped carbon material adsorbed with iron ions is obtained;The nitrogen-doped carbon material adsorbed with iron ions is placed in inert atmosphere and reduced, and the multi-level hole defect carbon load single atom oxygen reduction electrocatalyst is obtained, and it is recorded as Fe / NC electrocatalyst.In the application, Fe is uniformly dispersed on carbon substrate in the form of single atom without the existence of Fe metal particles, which indicates that Fe is completely doped into carbon structure, and the existence of porous structure is beneficial to the exposure of Fe-N4 active site, so as to improve the oxygen reduction performance of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalyst technology, and in particular to a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst and its preparation method. Background Technology

[0002] The oxygen reduction reaction (ORR) is fundamental to novel clean, efficient, and green devices, including proton exchange membrane fuel cells (PEMFCs) and metal-air batteries. The ORR kinetics at the cathode of these batteries are slow during operation, thus requiring highly efficient electrocatalysts to accelerate the reaction. Currently, platinum-based catalysts remain the preferred ORR catalysts. However, the scarcity and high price of platinum, along with its poor methanol tolerance, severely hinders the development of clean energy. Therefore, developing efficient, inexpensive, and methanol-poison-resistant ORR catalysts to replace Pt-based materials is crucial, but also presents significant challenges.

[0003] In recent years, single-atom catalysts have been widely used in electrocatalytic reactions due to their extreme atom utilization, high catalytic activity, and selectivity. However, the high specific surface energy of single atoms makes them prone to migration and aggregation, posing significant challenges in their preparation. Conventionally, the anchoring effect of heteroatoms (boron, nitrogen, oxygen, sulfur, etc.) doped onto a support at high temperatures has been used to achieve efficient and stable dispersion of single-atom iron, which greatly improves iron utilization. However, due to the high surface energy of metal atoms, coordination with heteroatoms alone is insufficient to effectively fix metal atoms during pyrolysis, leading to metal ion aggregation, which significantly reduces the metal loading of single-atom catalysts. Therefore, exploring feasible methods to mitigate metal aggregation and obtain highly loaded single-atom catalysts remains challenging. Existing technologies require further improvement and development. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst and its preparation method, aiming to solve the problems of low atom utilization and poor catalytic activity of existing oxygen reduction electrocatalysts.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a carbon-supported single-atom oxygen reduction electrocatalyst with hierarchical porous defects, comprising the following steps:

[0007] High-temperature pyrolysis of ZIF-8 containing NH4Cl yielded nitrogen-doped carbon with a porous structure.

[0008] The porous nitrogen-doped carbon was immersed in a solution containing ferric chloride to obtain a nitrogen-doped carbon material adsorbed with iron ions.

[0009] The nitrogen-doped carbon material adsorbed with iron ions was subjected to reduction treatment in an inert atmosphere to obtain a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, denoted as Fe / NC electrocatalyst.

[0010] The method for preparing the multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, wherein the high-temperature pyrolysis treatment of ZIF-8 containing NH4Cl is performed at a temperature of 600-1000℃.

[0011] The method for preparing the multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, wherein the inert atmosphere is one or more of nitrogen, helium and argon.

[0012] A multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst is prepared by the preparation method of the multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst described in this invention.

[0013] Beneficial effects: Compared with the prior art, this invention provides a method for preparing a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst. First, NH4Cl is decomposed into NH3 and HCl at high temperature. ZIF-8, as an acid-sensitive material, can be etched by the HCl formed during the decomposition process. Combined with the departure of Zn, a porous nitrogen-doped carbon structure is ultimately formed. Then, at room temperature, Fe... 3+ Fe can combine with vacancies on the pore surface to form a stable Fe-N structure. Subsequently, the carbon material adsorbed with metal ions is reduced again in an inert atmosphere, thus achieving atomic-level dispersion of Fe-N4 on the nitrogen-doped porous carbon surface, thereby preparing a hierarchical porous defect carbon-supported single-atom oxygen reduction electrocatalyst. In this invention, Fe is uniformly dispersed on the carbon substrate in single-atom form without the presence of Fe metal particles, indicating that Fe is completely doped into the carbon structure. The presence of the porous structure is beneficial to the exposure of Fe-N4 active sites, thereby improving the oxygen reduction performance of the catalyst. Attached Figure Description

[0014] Figure 1 In the image, a and b are SEM images of NH4Cl@ZIF-8 at 500 nm and 200 nm, respectively, while c and d are TEM images of NH4Cl@ZIF-8 at 100 nm and 50 nm, respectively.

[0015] Figure 2 EDX spectrum of NH4Cl@ZIF-8.

[0016] Figure 3In the image, a represents the preparation process of the hierarchical porous defect carbon-supported single-atom FeN4 sites, b is the SEM image of Fe / NC, c is the TEM image of Fe / NC, d is the HR-TEM image of Fe / NC, e is the EDS elemental distribution map of Fe / NC, f and g are the HAADF-STEM images of Fe / NC at 2 nm and 1 nm conditions, respectively, and h is the EELS image of Fe / NC.

[0017] Figure 4 In the figure, a is the XRD comparison map of each sample, b is the Raman comparison map of each sample, and c is the infrared spectrum comparison map of each sample.

[0018] Figure 5 N2 adsorption / desorption isotherms of nitrogen-doped carbon substrates before and after the addition of NH4Cl.

[0019] Figure 6 In the image, a is the XPS spectrum of Fe / NC, b is the high-resolution C XPS spectrum of Fe / NC, c is the high-resolution Fe XPS spectrum of Fe / NC, and d is the high-resolution N XPS spectrum of Fe / NC.

[0020] Figure 7 In the figure, a is the X-ray absorption spectrum of Fe / NC and standard Fe foil, Fe2O3; b is the XAFS oscillation curve of Fe / NC and standard Fefoil, Fe2O3 with respect to Fe d extension; c is the experimental and fitting data graph of the XAFS spectrum of Fe / NC with FT Fourier transform; and d is the Fe-N4 structure diagram of Fe / NC.

[0021] Figure 8 In the figure, a and b are the LSV curves and corresponding Tafel slopes of different catalysts and Pt / C at 1600 rpm, respectively; c is the LSV curve of Fe / NC; and d is the KL fitting graph of Fe / NC.

[0022] Figure 9 In the figure, a represents the kinetic current density of each catalyst at different potentials, b represents the hydrogen peroxide content and the number of transferred electrons of Fe / NC and Pt / C in the ORR process, the kinetic current density of each catalyst at different potentials, the LSV curve of Fe / NC, and c and d represent the experimental results of Fe / NC and Pt / C's resistance to methanol interference and stability, respectively.

[0023] Figure 10 In the figure, a is the CV curve of Fe / NC, b is the CV curve of Fe / NC (ZIF-8), c is the CV curve of NC, and d is a comparison of the double layer capacitance of each catalyst. Detailed Implementation

[0024] This invention provides a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0025] Studies have shown that defect sites on the support play a significant role in the synthesis of high-performance single-atom catalysts. The unique electronic structure of the defect sites and their surrounding coordination environment can enhance the interaction between the metal and the support or promote the formation of unique coordination structures between the single atom and surrounding atoms. This special property between the defect structure and the single atom can effectively capture metal species and anchor them to the support, thereby enabling the synthesis of highly efficient single-atom catalysts.

[0026] Based on this, the present invention provides a method for preparing a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, comprising the following steps:

[0027] S10. ZIF-8 containing NH4Cl is subjected to high-temperature pyrolysis at 600-1000℃ to obtain nitrogen-doped carbon with a porous structure.

[0028] S20. The porous nitrogen-doped carbon is immersed in a solution containing ferric chloride to obtain a nitrogen-doped carbon material adsorbed with iron ions.

[0029] S30. The nitrogen-doped carbon material adsorbed with iron ions is placed in an inert atmosphere for reduction treatment to obtain a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, denoted as Fe / NC electrocatalyst.

[0030] Specifically, this embodiment provides a pyrolysis strategy assisted by NH4Cl to prepare a porous Fe single-atom catalyst. First, high-temperature pyrolysis of ZIF-8 containing NH4Cl (NH4Cl@ZIF-8) is used, which causes the Zn atoms within the micropores to evaporate and the NH4Cl etching to form numerous pores. Figure 1 Chinese AD and Figure 2 As can be seen, NH4Cl@ZIF-8 retains the dodecahedral structure of ZIF-8, and NH4Cl is successfully trapped within the porous ZIF-8, similar to the encapsulation of metal chlorides within ZIF-8. In this step, NH4Cl decomposes into NH3 and HCl above 160℃. ZIF-8, being an acid-sensitive material, can be etched by the HCl formed during decomposition, and with the departure of Zn, a porous nitrogen-doped carbon structure is ultimately formed. Next, the porous nitrogen-doped carbon is immersed in a solution containing ferric chloride. The micropores on the carbon support can trap free iron ions, resulting in a nitrogen-doped carbon material adsorbed with iron ions. In this step, Fe...3+ It can combine with vacancies on the pore surface to form a stable Fe-N structure; finally, the carbon material adsorbed with metal ions is reduced again in an inert atmosphere to achieve atomic-level dispersion of Fe-N4 on the nitrogen-doped porous carbon surface (denoted as Fe / NC). The preparation process is as follows: Figure 3 As shown in Figure a.

[0031] Figure 3 Figures b and c show that the average size of the obtained Fe / NC catalyst is approximately 100 nm. Compared to the precursor NH4Cl@ZIF-8, the structure of Fe / NC has changed somewhat. This is due to the low boiling points (906 °C) of NH4Cl and zinc atoms in the precursor. NH4Cl decomposes at high temperatures into NH3 and HCl gases that etch the carbon substrate, while the evaporation of zinc also leads to an increase in defects and pore structures in the carbon substrate. High-magnification transmission electron microscopy (such as...) shows... Figure 3 As shown in Figure d), the formation of a porous structure further confirms the above reasoning. Furthermore, the presence of the porous structure facilitates the exposure of Fe-N4 active sites, thereby improving the oxygen reduction performance of the catalyst. EDS mapping diagram (as shown in Figure d) Figure 3 As shown in Figure e), C, N, and Fe are uniformly distributed in the Fe / NC material. Furthermore, spherical aberration electron microscopy (such as...) Figure 3 The results (shown in f and g) clearly show that Fe is uniformly dispersed on the carbon substrate in the form of single atoms, without the presence of Fe metal particles, indicating that Fe is completely doped into the carbon structure. This result is consistent with the XRD results. Electron energy loss spectroscopy (EELS) further confirms the presence of N and Fe elements on the carbon substrate.

[0032] This embodiment also investigated the basic phases and crystallinity of the obtained Fe / NC material with carbon defects using X-ray diffraction (XRD) and Raman spectroscopy. Figure 4 As can be seen from Figure a, the XRD shows two distinct characteristic peaks for Fe / NC at approximately 24.8° and 44°, which are attributed to the graphite carbon structure at (002) and (101) respectively, without any obvious diffraction peaks of crystalline metals or metal compounds, ruling out the possibility of metal agglomeration. 1 At the same time, Figure 4 The Raman spectrum in middle b shows 1354 and 1584 cm⁻¹. -1 The dominant frequency bands correspond to the D band of the disordered carbon structure and the ordered sp band, respectively. 2 The G-band of hybrid carbon. Among them, I... D / I G This can be used to evaluate the degree of graphitization of the obtained material. Notably, the decomposition of NH4Cl effectively increases the defect level of the nitrogen-doped carbon (NC) substrate material, which is beneficial for Fe atom anchoring. The properties of the NC substrate are further demonstrated by infrared spectroscopy (e.g., Figure 4 (as shown in c).

[0033] This embodiment also uses BET to test the specific surface area and pore size distribution characteristics of the NC catalyst. Figure 5 The N2 adsorption / desorption isotherms of the nitrogen-doped carbon substrates before and after the addition of NH4Cl are shown. Both exhibit typical Type IV curves, indicating that NC possesses a hierarchical porous structure. The specific surface areas of NC and NC(ZIF-8) are 10¹⁰.⁸ m², respectively. 2 g -1 and 689.5m 2 g -1 This indicates that the introduction of NH4Cl increased the specific surface area of ​​the NC substrate and generated more anchoring points.

[0034] This embodiment investigated the electronic structure of atoms in Fe / NC, such as... Figure 6 As shown in Figure a, the XPS full spectrum of Fe / NC reveals that the material is composed of C, N, and Fe. The high-resolution spectrum of C (as shown in Figure a) is also presented. Figure 6 Figure b) shows the positions of three peaks at 284.8, 285.8, and 289.6 eV, corresponding to the CC, CN, and OC=O species, respectively, confirming the successful incorporation of nitrogen into the carbon substrate. Figure 6 The high-resolution XPS spectrum of Fe in c showed a low Fe content, with a peak at approximately 711.2 eV attributed to the Fe 2p3 / 2 orbital, indicating the presence of Fe-N. x Catalytic active sites. Fe-N x The presence of bonds can also be detected by high-resolution XPS spectra of N (e.g., Figure 6 As shown in d), this is confirmed.

[0035] Synchrotron radiation X-ray absorption spectroscopy is crucial for studying local atomic and electronic structures, and in this example, the electrocatalyst Fe / NC was used in the study. XAFS was first used to explore the X-ray absorption spectrum of the Fe / NC electrocatalyst (results are shown in Figure 1). Figure 7 As shown in Figure a), Fe is in an oxidized state, a result highly consistent with Fe XPS. Secondly, the local electronic structure was investigated (results are shown in Figure a). Figure 7 As shown in Figure b), the Fe / NC electrocatalyst only... The presence of an Fe-O shell similar to that of the Fe2O3 standard, without the detection of Fe-Fe peaks, indicates that the product obtained from Fe atoms exists in a monodisperse state. (The text abruptly ends here.) Figure 7 Experimental and fitting data from the XAFS spectra of Fe / NC with respect to the Fourier transform of Fe further confirm that there is only a single Fe-N coordination bond, which demonstrates that iron atoms exist in a single-atom dispersion in the obtained product. Fitting calculations show that there are four N atoms around each Fe atom, forming a FeN4 structure (e.g., Figure 7 (as shown in d).

[0036] Carbon-based catalysts typically operate under alkaline conditions, while the oxygen reduction reaction is crucial in neutral media. LSV curves were used to further explore the catalytic mechanisms of all samples. Figure 8 As can be seen from Figure a, the Fe / NC catalyst exhibits superior electrochemical performance, with a higher half-wave potential (Ea). 1 / 2 The voltage (V) was 0.851, which is more positive than that of the commercial Pt / C catalyst (0.828 V). Furthermore, the Fe / NC catalyst exhibited a voltage (V) of 5.74 mA cm⁻¹. -2 The maximum limiting diffusion current density is higher than that of the Fe / NC(ZIF-8) catalyst (5.01 mA cm⁻¹). -2 ), and commercial Pt / C catalyst (5.11 mA cm⁻¹) -2 This indicates that reasonable and effective porous Fe / NC co-doping has a catalytic effect on ORR performance. LSV was obtained from the polarization curves. Figure 8 The Tafel plot in section b also shows the excellent catalytic performance of Fe / NC, with a slope of 50.63 mV dec. -1 Less than commercially available Pt / C (55.75mV dec) -1 This indicates its favorable ORR kinetics. The kinetic current density at different potentials further validates the excellent kinetic performance of Fe / NC. To elucidate the ORR catalytic mechanism of Fe / NC, the LSV curves of the catalyst were tested by RDE at different rotational speeds (400 to 1600 rpm) (e.g., Figure 8 As shown in Figure c), it is confirmed that the limiting current density increases with increasing rotational speed during the dynamic process. Based on the KL fitting graph, Figure 8 The results showed a good parallel linear relationship, and the calculated number of transferred electrons n was approximately 4.08, indicating that the Fe / NC catalyst follows first-order reaction kinetics.

[0037] At different potentials, the Fe / NC electrocatalyst maintained the best kinetic current density, which further proves that Fe / NC has good kinetics (e.g., Figure 9 (As shown in Figure a). Furthermore, the n value of the catalyst and the H2O2 yield in ORR were calculated using the ring current and disk current recorded by the RRDE test, as shown in Figure a. Figure 9 As shown in Figure b, within the effective voltage range, the electron transfer number of the FeNC catalyst is consistently greater than 3.83 and the H2O2 rate is consistently less than 8.6%, which is very close to the results of commercial Pt / C catalysts (3.83–3.98). These test results demonstrate that the Fe / NC catalyst proceeds via a four-electron transfer pathway during catalysis, reducing the possibility of the intermediate product H2O2 negatively impacting the catalyst.

[0038] Co-doping is beneficial for improving the electrochemical active area tolerance of the catalyst, which is another key criterion for evaluating the long-term operating performance of cathode catalysts in applications. Methanol tolerance is determined by the It test before and after adding 3M methanol to an O2-saturated aqueous solution. Figure 9 As shown in Figures c and d, after methanol injection, the current density on the electrode of the commercial Pt / C catalyst immediately decreases, indicating a loss of catalytic activity. In contrast, the oxygen reduction current intensity of the Fe / NC catalyst decreases slightly before recovering. This tolerance demonstrates that the Fe / NC catalyst exhibits strong resistance to the cross-reaction of methanol. At a given potential, chronoamperometry shows that Fe / NC exhibits better stability compared to commercial Pt / C. These results indicate that the Fe / NC catalyst possesses stable metal-nitrogen active sites, which not only inhibit the structural collapse or pore deformation of carbon-based materials, preventing the aggregation of surface metal particles, but also enhance the catalytic activity and long-term stability of the catalyst. Therefore, the Fe / NC catalyst can serve as an excellent low-cost alternative to cathode catalysts, thereby improving the overall performance of the battery.

[0039] Furthermore, the C of the catalyst can be obtained by performing double-layer capacitance tests within the non-Radial voltage range where ORR does not occur. dl Result. For example. Figure 10 As shown in Figure 1, the C values ​​of the prepared catalysts are... dl They are 16.71mF cm -2 10.24mF cm -2 and 6.36mF cm -2 The Fe / NC catalyst exhibits the highest double-layer capacitance, indicating that rational and effective Fe / NC co-doping is beneficial for improving the electrochemical active surface area of ​​the catalyst, thereby accelerating the mass transfer process and ultimately enhancing its ORR catalytic activity. The superiority of the Fe / NC catalyst is further confirmed by BET, with its high specific surface area and hierarchical porous structure. These characteristics all indicate that this structure is conducive to the exposure of catalytic sites. Experimental results show that the catalyst not only possesses a hierarchical porous structure, a large specific surface area, and abundant pore defects.

[0040] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, characterized in that, Including the following steps: High-temperature pyrolysis of ZIF-8 containing NH4Cl yielded nitrogen-doped carbon with a porous structure. The porous nitrogen-doped carbon was immersed in a solution containing ferric chloride to obtain a nitrogen-doped carbon material adsorbed with iron ions. The nitrogen-doped carbon material adsorbed with iron ions was subjected to reduction treatment in an inert atmosphere to obtain a multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, denoted as Fe / NC electrocatalyst.

2. The preparation method of the multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst according to claim 1, characterized in that, In the step of high-temperature pyrolysis treatment of ZIF-8 containing NH4Cl, the temperature of high-temperature pyrolysis treatment is 600-1000℃.

3. The method for preparing the multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst according to claim 1, characterized in that, The inert atmosphere is one or more of nitrogen, helium, and argon.

4. A multi-level porous defect carbon-supported single-atom oxygen reduction electrocatalyst, characterized in that, The catalyst was prepared using the method described in any one of claims 1-3 for preparing a single-atom oxygen reduction electrocatalyst supported on a multi-level porous defect carbon.

Citation Information

Patent Citations

  • Metal monatomic catalyst and preparation method thereof

    CN111420691A

  • Defect-rich carbon material as well as preparation method and application thereof

    CN113697791A